Caliphate and kingship in a fifteenth-century literary history of Muslim leadership and pilgrimage = Al- Ḏahab al-masbūk fī ḏikr man ḥaǧǧa min al-ḫulafāʾ wa-l-mulūk - Maqrīzī, Aḥmad Ibn-ʿAlī al- 1364-1442 (Bibliotheca Maqriziana, 2016)
In 'Caliphate and Kingship in a Fifteenth-Century Literary History of Muslim Leadership and Pilgrimage' Jo Van Steenbergen presents a new study, edition and translation of 'al-Dahab al-Masbuk fi Dikr man Hagga min al-Hulafa' wa-l-Muluk', a summary history of the Muslim pilgrimage to Mecca by al-Maqrizi (766-845 AH/ca. 1365-1442 CE). Traditionally considered as a useful source for the history of the 'hagg, al-Dahab al-Masbuk' is re-interpreted here as a complex literary construction that was endowed with different meanings. Through detailed contextualist, narratological, semiotic and codicological analyses Van Steenbergen demonstrates how these meanings were deeply embedded in early-fifteenth century Egyptian transformations, how they changed substantially over time, and how they included particular claims about authorship and about legitimate and good Muslim rule